2022
DOI: 10.3389/fonc.2022.861412
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of a m7G-Related Gene-Based Prognostic Model for Gastric Cancer

Abstract: BackgroundGastric cancer (GC) is one of the most common malignant tumors of the digestive system. Chinese cases of GC account for about 40% of the global rate, with approximately 1.66 million people succumbing to the disease each year. Despite the progress made in the treatment of GC, most patients are diagnosed at an advanced stage due to the lack of obvious clinical symptoms in the early stages of GC, and their prognosis is still very poor. The m7G modification is one of the most common forms of base modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The interaction between Gemin5 and the cap-binding protein eIF4E [46] as well as the direct recognition of the cap structure of snRNAs by Gemin5 [15] prompted us to seek the involvement of Gemin5 in RNA cap-binding complexes. Recent studies identified Gemin5 as one of the m 7 G methylation-related genes, also including CYFIP1, EIF4E2, EIF4E1B, EIF4G3, NCBP2, NUDT10, NUDT4, WDR4, METTL1, and DCP s. These genes are biomarkers for predicting overall survival outcomes in hepatocellular carcinoma and gastric cancer [48] , [49] . Noteworthy, Gemin5 knockout has been shown to be detrimental in animal models, including mouse and drosophila [17] , [24] .…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between Gemin5 and the cap-binding protein eIF4E [46] as well as the direct recognition of the cap structure of snRNAs by Gemin5 [15] prompted us to seek the involvement of Gemin5 in RNA cap-binding complexes. Recent studies identified Gemin5 as one of the m 7 G methylation-related genes, also including CYFIP1, EIF4E2, EIF4E1B, EIF4G3, NCBP2, NUDT10, NUDT4, WDR4, METTL1, and DCP s. These genes are biomarkers for predicting overall survival outcomes in hepatocellular carcinoma and gastric cancer [48] , [49] . Noteworthy, Gemin5 knockout has been shown to be detrimental in animal models, including mouse and drosophila [17] , [24] .…”
Section: Resultsmentioning
confidence: 99%
“…Li et al. ( 33 ) have also done related work, but our analysis is more in-depth and comprehensive than their study. First of all, compared with that literature, this study analyzed the somatic mutations of m7GRGs in GC patients, including SNV and CNV.…”
Section: Discussionmentioning
confidence: 99%
“…As a part of a scaffold component of eukaryotic translation initiation factor 4F, eukaryotic translation initiation factor 4G 1 (EIF4G1) is closely associated with various tumors, especially in solid tumors [ 27 ]. Nudix hydrolase 10 (NUDT10), located in Xp11.22, increases promoter methylation and is associated with OS in prostate cancer and gastric cancer [ 28 , 29 ]. NUDT10 and Nudix hydrolase 11 (NUDT11) can promote prostate carcinogenesis and increase prostate cancer susceptibility by being involved in a variety of biological processes and mediating cellular stress responses [ 30 ].…”
Section: Discussionmentioning
confidence: 99%